Bilateral double-headed condyles: A rare case report - Swati Phore; Rahul R Singh; Mitali Malhotra (Wolters Kluwer Medknow Publications, 2018)
Bifid mandibular condyle is characterized by the duplicity of the head of the mandibular condyle, so the name double-headed condyle. It is usually diagnosed on routine radiographic examination and is described as a rare entity. Usually, bifid condyle is an incidental finding and its etiology is controversial, with no predilection for sex or ethnic background. Herein, we report a case of bilateral bifid condyles.